Diffusive‐Dispersive Isotope Fractionation of Chlorinated Ethenes in Groundwater: The Key Role of Incomplete Mixing and Its Multi‐Scale Effects. Issue 4 (24th April 2023) - Wienkenjohann, Henning; Jin, Biao; Rolle, Massimo
Abstract: Diffusive‐dispersive processes are ubiquitous in porous media with important implications for solute transport in many natural and engineered systems; however, their effects on isotope fractionation of organic contaminants in subsurface flow‐through systems is not well understood. In this study, we investigate the propagation of isotope shifts in groundwater systems, induced by lateral diffusive‐dispersive isotope fractionation, on carbon and chlorine isotope signatures of chlorinated ethene plumes at steady state. We consider three distinct spatial scales (i.e., pore, laboratory, and field scales) and explore isotope fractionation with high‐resolution pore‐scale simulations, flow‐through experiments, and field‐scale numerical modeling. The experimental lab‐scale investigation was carried out using cis‐dichloroethene (cis‐DCE) as model contaminant, whereas cis‐DCE and trichloroethene (TCE) were considered in the multi‐scale numerical simulations. The pore‐scale analysis of transverse displacement demonstrates significant isotope fractionation over a wide range of seepage velocities (0.1–10 m/day). The pore‐scale simulations illuminate the key role of incomplete mixing, which sustains isotopologue‐specific gradients in the pore channels and results in the strongest isotope fractionation (−6‰ for carbon; −10‰ for chlorine) at the fastest flow velocity. The outcomes of the flow‐through experiments support the key role of isotopologue‐specific aqueous diffusion also at the laboratory scale, where significant diffusive‐dispersive isotopic shifts were observed at the outlet of the setup. Finally, the detailed field‐scale numerical simulations, performed in a cross‐section of a heterogeneous aquifer, illustrate that the microscopic diffusion‐induced isotope fraction propagates at macroscopic scales. Key Points: Pore‐scale simulations show diffusive isotope fractionation of TCE and cis‐DCE in a broad range of groundwater flow velocities Incomplete mixing at high flow velocity results in steep isotopologue concentration gradients in the pore channels causing strong isotope fractionation High‐resolution laboratory experiments and field‐scale simulations show that isotope fractionation propagates at macroscopic scales